The Influence of Capital Structure and Dividend Policy on Company Value in the Manufacturing Sector on the Indonesian Stock Exchange - Monalisa; Taliding, Arianto; Nur Mega (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
This research aims to examine the influence of capital structure and dividend policy on company value in the manufacturing sector on the Indonesia Stock Exchange in 2013-2015. This research is quantitative research with a causality approach. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2013-2015 according to the publication of the Indonesian Capital Market Directory (ICMD) using a purposive sampling technique. The data used in this research is secondary data based on the collection of financial report data from manufacturing companies listed on the Indonesia Stock Exchange for the 2013-2015 period. Data analysis uses multiple linear regression analysis.The research results show that: 1) capital structure and dividend policy have a simultaneous effect on company value, 2) capital structure has a positive and significant effect on company value and 3) dividend policy has a negative and insignificant effect on company value. This means that capital structure and dividend policy influence the value of companies in the manufacturing sector on the Indonesia Stock Exchange in 2013-2015.